Contextualizing Poda Na Lima As An Ethnopedagogical Framework for PAI BP in Indonesian Elementary Schools - Fuji Pratami; Willy Akmansyah Lubis; M Yemmardotillah; Nahid Ayad; Rina Juliana (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Efforts to strengthen character education through local wisdom have become a national priority, yet no empirical studies have developed an operational model for integrating Poda Na Lima into Islamic Education and Character Education (PAI BP) at the elementary level. Consequently, Mandailing cultural wisdom remains underutilized as a pedagogical foundation. This study aims to develop, implement, and evaluate an ethnopedagogical model grounded in Poda Na Lima for PAI BP instruction in elementary schools in Mandailing Natal Regency. Using a qualitative approach with an educational ethnography and multiple case study design, the research involved PAI BP teachers through interviews, participant observation, and document analysis. This approach enabled an in depth understanding of how cultural values are negotiated and internalized in classroom interactions. Findings show that integrating Poda Na Lima values Paias Rohamu, Paias Pamatangmu, Paias Parabitonmu, Paias Bagasmu, and Paias Pakaranganmu can be effectively implemented through structured habituation, spiritual reinforcement, and culturally responsive communication. The model contributes to students’ religious, social, and ecological character development and supports the strengthening of Mandailing cultural identity. However, challenges persist, including the lack of standardized curriculum guidelines and limited teacher competence in ethnopedagogy. This study offers a theoretically grounded ethnopedagogical model that connects local wisdom with Islamic and character education. Practically, it provides an applicable framework that teachers and policymakers can adopt to design more contextualized and culturally relevant PAI BP learning in diverse Indonesian educational settings.